KEPEMIMPINAN PENDIDIKAN PADA DAYAH BUSTANUL ARIFIN BENER MERIAH - Yuyun Wahyuni (AL-ILMU, 2022)
The leadership of Dayah education is a role in efforts related to activities or processes of educating and teaching on the one hand, and on the other hand related to efforts to develop educational knowledge and the implementation of education and teaching, both in traditional and modern integrated Dayah, so that activities the activities carried out can be more effective and efficient in achieving the goals of education, religious and general learning. Educational leadership as an ability and process of influencing, mobilizing, coordinating, and guiding people who have to do with the development of educational science and the implementation of education and teaching. The leadership function of Dayah requires a leader to act as a liaison between Dayah and interested outside parties, conflicts that occur or differences in interests in the Dayah institution require the presence of a leader in solving existing problems, there are five essential leadership functions , namely the function of determining direction, function of spokesperson, function of communicator, function of mediator, and function of integrator. Educational leadership has 10 (ten) qualifications: namely: Fair, Trustworthy, Sincere, Work hard and earnestly. Have high integrity. Have high guts, Assertive, Able to communicate, Honest and open, Patient.